FEATURES OF COMPONENTS OF BIOLOGICAL SCHOOL EDUCATION - Korshevnyuk, Tetyana V. (Educological discourse, 2016)
In this article cognitive, activity and personal components of thecontent of school biology education at the present stage of its development aresubstantiated on the basis of the theoretical analysis. There are also shown theirfeatures in the context of trends in the renovation of science education. Analysis of the biological component of «Natural Science» educational field in theState Standard, curriculum and biology’s textbooks, based on the implementation ofthese components has allowed defining their contribution to achieving the objectivesbiology education of secondary schools students. The relevance and the prospect ofthe content of school biological education constructing, based on the combinationof natural science and humanitarian aspects are also specified in the article.